Exploring types of waste generated: a study of construction industry of Pakistan - Akhund, Muhammad Akram; Memon, Aftab Hameed; Memon, Nafees Ahmed; Ali, Tauha Hussain; Khos, Ali Raza; Imad, Hafiz Usama (Penerbit Universiti Kebangsaan Malaysia, 2019)
The construction sector is responsible for providing fundamental physical structure required for living and survival of human life. Increased development works have led in resulting the massive amount of waste generation in developing countries. Due to poor management system on sites, it has become more crucial and exerts several negative impacts on society and the environment. This Unused waste material has a negative impact on the ecosystem and needs a considerable amount of money for recycling, reusing and disposal of the waste. Like other developing countries Pakistan is spending a significant portion of its GDP on handling construction waste. Among the several other factors, the key contributes are highlighted in this study. This study is exploratory work investigating the types of construction waste generated on site and their relative impact of the project cost in construction projects of Pakistan. Through questionnaire the opinion of clients, consultant and constructor have been taken to identify the major types of waste having more impacts on cost and time. Through Average index, severity index and importance index, the probability of occurrence of waste through different materials, severity level of waste production by these materials, and the overall effect of all waste generating materials have been found respectively. Among the materials sand, concrete, tile is the most common materials, which are responsible for a waste generation while time and cost are the two most common non-physical waste generating factors.